2015
DOI: 10.1097/jcp.0000000000000372
|View full text |Cite
|
Sign up to set email alerts
|

Medication Nonadherence, “Professional Subjects,” and Apparent Placebo Responders

Abstract: Nonadherence is a major problem in clinical trials of new medications. To evaluate the extent of nonadherence, this study evaluated pharmacokinetic sampling from 1765 subjects receiving active therapy across eight psychiatric trials conducted between 2001 and 2011. With nonadherence defined as > 50% of plasma samples below the limit of quantification for study drug, the percentage of nonadherent subjects ranged from 12.8% to 39.2%. There was a trend toward increased nonadherence in studies with greater numbers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
67
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(73 citation statements)
references
References 61 publications
4
67
0
2
Order By: Relevance
“…The study drug concentration among the mDOT group (71.9%) is consistent with the McCann et al study, which showed nonadherence rates of 12.8-39.2% [2]. Deceptively removing pills to feign higher adherence leads to the low rates of nonadherence typically measured by pill count, as seen in the aforementioned study (0.0-5.1% [2]) and in the present study (0-3%). The discrepancy between the adherence rates reported by pill count and those measured through pharmacokinetic sampling is substantial.…”
Section: Discussionsupporting
confidence: 91%
“…The study drug concentration among the mDOT group (71.9%) is consistent with the McCann et al study, which showed nonadherence rates of 12.8-39.2% [2]. Deceptively removing pills to feign higher adherence leads to the low rates of nonadherence typically measured by pill count, as seen in the aforementioned study (0.0-5.1% [2]) and in the present study (0-3%). The discrepancy between the adherence rates reported by pill count and those measured through pharmacokinetic sampling is substantial.…”
Section: Discussionsupporting
confidence: 91%
“…Increased participation of volunteers who pretend to have depression may contribute to the increasing failure rate in MDD trials (28, 29). Participants who feign depression and then answer truthfully during the medication trial will appear to be responders in both the placebo and the treatment arm, which can reduce statistical power and effect size (32). Failed trials may cause inappropriate discontinuation of the development of potentially effective medications (32).…”
Section: Discussionmentioning
confidence: 99%
“…Although there are no practical instruments to detect malingering (34) or to flag volunteers who misrepresent their health histories, several strategies to mitigate deception by research volunteers have been proposed (10, 30, 32, 36–38). They are summarized in Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…DOT is therefore often used in Phase I trials with healthy volunteers, but rarely used in Phase II–Phase IV trials with ambulatory patients. McCann et al summarised “DOT‐proxy” methods, including using camera/video‐enabled mobile phone technology where participants record ingestion and transmit the images to investigators for observation (eg AiCure Technologies, Inc.), which may be somewhat burdensome for both parties. DOT methods could be used to assess all three phases of nonadherence in the clinical trial setting, as defined by EMERGE.…”
Section: Identifying Appropriate Adherence Measuresmentioning
confidence: 99%
“…However, such monitoring is sensitive to bias when participants ingest the investigational drug before a trial visit, even if they may have been nonadherent in the period running up to the visit (white‐coat adherence) . Monitoring the investigational drug in biologic fluids is also restricted to active arms of the trial, unless an ultralow dose of the drug, which is detectable but below the lower end of the therapeutic range, is used in the control arm . An alternative is to use other pharmacologically inactive biologic markers that are ingested simultaneously with the investigational or placebo compounds.…”
Section: Identifying Appropriate Adherence Measuresmentioning
confidence: 99%